Modulation of the intestinal microbiota and the metabolites produced by the administration of ice cream and a dietary supplement containing the same probiotics - Da Cruz Rodrigues, Vivian Cristina; Rocha Faria Duque, Ana Luiza [UNESP]; De Carvalho Fino, Luciana; Simabuco, Fernando Moreira; Sartoratto, Adilson; Cabral, Luc lia; Noronha, Melline Fontes; Sivieri, Katia [UNESP]; Antunes, Adriane Elisabete Costa (Cambridge University Press (CUP), 2020)
The aim of the present work was to compare the capacity to modulate the intestinal microbiota and the production of metabolites after 14 d administration of a commercial dietary supplement and a manufactured ice cream, both containing the same quantity of inulin and the same viable counts of Lactobacillus acidophilus LA-5 and Bifidobacterium animalis BB-12, using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) model. Samples of the colonic contents were evaluated microbiologically by real-time quantitative PCR (qRT-PCR) and next-generation sequencing and chemically by the production of SCFA (acetate, propionate and butyrate) and ammonium ions (NH 4 ). Statistical analyses were carried out for all the variables using the two-way ANOVA followed by the Tukey multiple comparisons test (P < 0-05) for metabolite production, qRT-PCR and the bioinformatics analysis for microbiota diversity. Dietary supplement and ice cream were able to deliver the probiotic L. acidophilus and B. animalis to the simulated colon and modulate the microbiota, increasing beneficial micro-organisms such as Bifidobacterium spp., Bacteroides spp. and Faecalibacterium spp. for dietary supplement administration, and Lactobacillus spp. for ice cream supplementation. However, the ice cream matrix was probably more favourable for the maintenance of the metabolic activity of the probiotics in the SHIME® model, due to the larger amounts of acetate, propionate, butyrate and ammonium ions obtained after 14 d of supplementation. In conclusion, both ways of probiotic supplementation could be efficient, each with its own particularities.
Keywords: Ammonia; Bifidobacterium animalis; Fatty acids; Lactobacillus acidophilus; SHIME®